IMPLEMENTASI INOVASI SISTEM LAYANAN PENGADUAN PUBLIK BERBASIS DIGITAL ( STUDI LAYANAN ADUAN ULAS DI KOTA SURAKARTA) - Wijayanto, Hendra (The Indonesian Journal of Public Administration (IJPA), 2024)
AbstractThis study discusses the implementation of digital-based public complaint service innovation through ULAS (Unit Layanan Aduan Surakarta) in the City of Surakarta. The innovation aims to improve the effectiveness of handling public complaints by utilizing information technology, enabling faster, more transparent, and accountable reporting, follow-up, and resolution processes. This research employed a descriptive qualitative method with data collected through interviews, observations, and document studies. The analysis was conducted based on indicators of bureaucratic structure, resources, communication, and disposition. The results show that ULAS facilitates the public in submitting complaints online, reduces administrative barriers, and strengthens coordination among local government agencies. However, challenges remain, such as limited digital literacy among some citizens, the need to enhance human resource capacity, and the maintenance of technological systems. In conclusion, the implementation of ULAS significantly contributes to improving public service quality, although its sustainability requires strengthening infrastructure, conducting extensive public outreach, and integrating cross-sector data to realize responsive and participatory public services in the City of Surakarta.Keywords: Implementation, ULAS, Complaint, Surakarta